PENGEMBANGAN MEDIA VIDEO DOKUMENTER PADA PEMBELAJARAN SKI DAULAH ABBASIYAH UNTUK CALON GURU - Hakim, Muhammad; Jasiah, Jasiah (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
This study aims to develop an instructional medium in the form of a documentary video to enhance the learning interest of pre-service teacher students in the Islamic Cultural History (SKI) course on the topic of the Abbasid Dynasty. The research employs the Research and Development (R&D) method with key stages including needs identification, media design, product development, and initial evaluation. The video development process utilizes artificial intelligence technologies such as ChatGPT for scriptwriting, Gemini AI for creating image illustrations, and CapCut for video editing, animation, and audio processing. The final product is an engaging, interactive, and informative documentary video that presents the history of the Abbasid Dynasty with modern visual style and easy-to-understand narration. The video not only delivers historical information but also fosters curiosity and active engagement among students during the learning process. Based on the initial evaluation, this media is considered effective in increasing attention and learning motivation among pre-service teacher students. The use of documentary videos is expected to become an innovative Islamic education learning medium that meets the needs of the digital generation and contributes positively to improving the quality of teaching and learning in higher education. ABSTRAK Penelitian ini bertujuan untuk mengembangkan media pembelajaran berbentuk video dokumenter guna meningkatkan minat belajar mahasiswa calon guru pada mata kuliah Sejarah Kebudayaan Islam (SKI) materi Daulah Abbasiyah. Penelitian menggunakan metode Research and Development (R&D) dengan tahapan utama meliputi identifikasi kebutuhan, perancangan media, pengembangan produk, dan evaluasi awal. Pengembangan video dilakukan dengan memanfaatkan teknologi berbasis kecerdasan buatan seperti ChatGPT untuk penyusunan narasi, Gemini AI untuk pembuatan ilustrasi gambar, dan CapCut untuk pengeditan video, animasi, serta pengolahan suara. Hasil pengembangan menghasilkan video dokumenter yang menarik, interaktif, dan informatif, yang menampilkan sejarah Daulah Abbasiyah dengan gaya visual modern dan narasi yang mudah dipahami. Video ini tidak hanya menyampaikan informasi sejarah, tetapi juga menumbuhkan rasa ingin tahu dan keterlibatan aktif mahasiswa dalam proses pembelajaran. Berdasarkan hasil evaluasi awal, media ini dinilai efektif dalam meningkatkan perhatian dan motivasi belajar mahasiswa calon guru. Penggunaan video dokumenter diharapkan dapat menjadi inovasi media pembelajaran PAI yang sesuai dengan kebutuhan generasi digital, serta memberikan kontribusi positif dalam peningkatan kualitas proses belajar mengajar di perguruan tinggi.